MXene‐Ti3C2 Armored Layer for Aluminum Current Collector Enable Stable High‐Voltage Lithium‐Ion Battery. Issue 22 (7th July 2022) - Yang, Shanglin; Li, Songmei; Du, Zhiguo; Du, Juan; Han, Chao; Li, Bin
Abstract: Elevating operating voltage (above 4.5 V) is a consequential approach to increasing the energy density of lithium‐ion batteries (LIBs). Unfortunately, the corrosion of cathode aluminum (Al) current collector at high voltage limits the application of high‐voltage LIBs. In this report, for the first time, MXene‐Ti3 C2 T x nanosheets are proposed as an armored layer for Al current collector to conquer the corrosion under high operating voltage over 4.5 V versus Li + /Li. The MXene armored layer is fabricated via a self‐assembly procedure, which exhibits ultra‐thinness less than 100 nm, attaches to Al substrate homogeneously, and ensures the electron conduction of current collector by virtue of outstanding conductivity. More importantly, the obtained MXene‐Al can be stabilized under a broad electrochemical window of 2–5.5 V versus Li/Li + in commercial LiPF6 ‐carbonates electrolyte. As a consequence, the execution of MXene‐Al current collector to ternary cathode LiCo1/3 Ni1/3 Mn1/3 O2 (NCM333) can significantly enhance electrochemical performance. Under a high cut‐off voltage of 4.5 V, the discharge capacity retention is increased from 21% to 81.4% after 300 cycles at 0.5 C with the protection of MXene armored layer. This work proposes an effective strategy for developing stable high‐voltage LIBs and contributes to the MXene application in energy‐related field. Abstract : An ultrathin MXene armored layer is fabricated on pure Al current collector (MXene‐Al) via a simple self‐assembly procedure. Obtained MXene‐Al current collector is electrochemically stable and has superior electrical conductivity in LiPF6 electrolyte, which is applied to high‐voltage lithium‐ion battery with a cut‐off voltage of 4.5 V.